Ministry Of Water Resources and Irrigation Ministerial Decree No. 208 Of The Year 2018 As Issued On 3/6/2018 Amending Some Articles of the Executive Regulations of Law No. 48 of the Year 1982 on Protecting the River Nile and Watercourses from Pollution, as Issued by Ministerial Decree No. 92 of the Year 2013 = وزارة الموارد المائية والرى قرار وزراى رقم 208 لسنة 2018 الصادر بتاريخ 3/6/2018 بتعديل بعض بنود اللائحة التنفيذية للقانون رقم 48 لسنة 1982 بشأن حماية نهر النيل والمجارى المائية من التلوث الصادر بالقرار الوزارى رقم 92 لسنة 2013 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic